Thermal stabilization of enterovirus A 71 and production of antigenically stabilized empty capsids. (23rd August 2022) - Kingston, Natalie J.; Shegdar, Mona; Snowden, Joseph S.; Fox, Helen; Groppelli, Elisabetta; Macadam, Andrew; Rowlands, David J.; Stonehouse, Nicola J.
Abstract : Enterovirus A71 (EVA71) infection can result in paralysis and may be fatal. In common with other picornaviruses, empty capsids are produced alongside infectious virions during the viral lifecycle. These empty capsids are antigenically indistinguishable from infectious virus, but at moderate temperatures they are converted to an expanded conformation. In the closely related poliovirus, native and expanded antigenic forms of particle have different long-term protective efficacies when used as vaccines. The native form provides long-lived protective immunity, while expanded capsids fail to generate immunological protection. Whether this is true for EVA71 remains to be determined. Here, we selected an antigenically stable EVA71 virus population using successive rounds of heating and passage and characterized the antigenic conversion of both virions and empty capsids. The mutations identified within the heated passaged virus were dispersed across the capsid, including at key sites associated with particle expansion. The data presented here indicate that the mutant sequence may be a useful resource to address the importance of antigenic conformation in EVA71 vaccines.